Fighting the death penalty : a fifty-year journey of argument and persuasion - Wanger, Eugene G. (Michigan State University Press, 2017)
Michigan is the only state in the country that has a death penalty prohibition in its constitution -- Eugene G. Wanger's compelling arguments against capital punishment is a large reason it is there. The forty pieces in this volume are writings created or used by the author, who penned the prohibition clause, during his fifty years as a death penalty abolitionist. His extraordinary background in forensics, law, and political activity as constitutional convention delegate and co-chairman of the Michigan Committee Against Capital Punishment has produced a remarkable collection. It is not only a fifty-year history of the anti-death penalty argument in America, it also is a detailed and challenging example of how the argument against capital punishment may be successfully made.